Online Political Communication - Giansante, Gianluca. author. aut Link
XV, 188 p. 28 illus., 20 illus. in color.
Keywords: This book provides research findings and practical information on online communication strategies in politics. Based on communication research and real-world political-campaign experience, the author examines how to use the Web and social media to create public visibility, build trust and consensus, and boost political participation. It offers a useful guide for practitioners working in the political arena, as well as for those managing communication projects in institutions or companies.